Effects of air content on rheological behavior and segregation of self-compacting concrete - Ferdaous Aghziel Sadfa; Mouhcine Ben Aicha; Olivier Jalbaud; Mounir Zaher; Adil Hafidi Alaoui; Yves Burtschell (Hybrid Advances)
Self-compacting concrete (SCC) offers significant advantages due to its low yield stress and plastic viscosity, yet challenges such as bleeding and segregation can compromise its stability. Maintaining a uniform aggregate distribution is essential to prevent these issues. Air-entraining admixtures (AEA) are often used to introduce air bubbles that enhance SCC's resilience in freeze-thaw conditions and potentially improve stability. This study addresses contradictions in prior research regarding the impact of entrained air on SCC's rheological behavior, experimentally evaluates the effects of varying air content on SCC's workability and segregation resistance, and establishes correlations between rheological characteristics and segregation stability. A comprehensive series of rheological tests, including slump flow diameter, flow time, blocking rate, segregation stability, plastic viscosity, yield stress, and segregation index, was conducted on SCC mixes with different AEA dosages. Regression models revealed significant correlations between air content and both the stability and workability of SCC, with results indicating that optimal AEA levels improve flowability and reduce segregation risks. These findings provide valuable insights into designing stable, high-performance SCC formulations tailored for challenging structural applications.